(untitled) (Conference Zone, 2022)
President of the Republic of Uzbekistan Przidnti Sh.M. Mirziyoyev has high intellectual potential in a speech to the Cabinet of Ministers dedicated to the main conclusions of 2020 and the most important priorities of socio-economic development of Uzbekistan in 2021, the introduction of innovation and innovative technologies in the preparation of competitive personnel is a promising way to form a perfect, highly educated person in all respects in the 1930’s. It is known that today all countries are trying to innovate as much as possible into education. Today’s news requires a organized, informal, public approach to them. Innovations are long-term investicides for the future. To stimulate interest in innovation and to educate a person who seeks to create innovation, education itself must be rich in innovation, where the spirit and environment of creativity must prevail. (Matthew 24:14; 28:19, 20) Today, the independent field of pedagogy—pedagogical innovation—is growing rapidly. Today, a number of initiatives are being undertaken in the countries of Central Asia. This is illustrated by the introduction of a system of innovative projects in our Republic, the implementation of a number of research works in the fields of innovation, innovative process, innovative work, and innovative management